Analisis Komunikasi Matematis Berdasarkan Kecemasan Tipe Ganda Mood dan Motoric pada Siswa Sekolah Dasar - Sari, Vany Diah Puspita; Fathurohman, Irfai; Sumaji, Sumaji (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2023)
The purpose of this study is to analyze the mathematical communication skills of students who have multiple types of anxiety, namely mood and motor types. This research was conducted using qualitative methods with the type of case study research. The research was conducted in class VI of Al-Hikmah Mayong Integrated Islamic elementary school in the 2022/2023 academic year. The instrument used is a non-test instrument in the form of interviews and documentation. Interviews were used to group students into 4 types of anxiety, namely mood, motoric, cognitive, and somatic. While the documentation used is the results of students' answers regarding mathematical communication tests, test questions are used to measure their mathematical communication. The technique used in the selection of informants is purposive sampling. The subjects used in this study were 2 students, this was because students had multiple types of mathematical anxiety, namely mood and motor types and other considerations. The data analysis used is 1) the data collection stage; 2) the data selection stage; 3) the data processing stage; 4) the data presentation stage, and; 5) the stage of conclusion. The results showed that students who had a dual type of mathematical anxiety in the mood and motoric types were unable to write text, were unable to draw, and were unable to use symbolic language. This is because students feel trembling and their hearts are pounding during mathematics learning, but students can communicate verbally well mathematically.